MgO-Lignin Dual Phase Filler as an Effective Modifier of Polyethylene Film Properties - Bula, Karol (Materials (Basel), 2020)
Functional magnesium oxide-lignin hybrid materials were obtained via mechanical grinding. Their particle shape and size as well as physicochemical properties were characterized. MgO-lignin materials with biocomponent content (between 20% and 80% amount of total weight of filler) were used as a partially bio-structured modifier of low density polyethylene. The composites with 5% by weight of dual fillers and polyethylene grafted with maleic anhydride were compounded in a twin screw extruder working in co-rotating mode. The prepared blends were cast extruded using a single screw extruder and laboratory cast line. The properties of the obtained films were verified in case of their weldability. The seal strength as well as shear test and tear strength of the welded sheets were examined. The results showed that the shortest equivalent time required to perform correct weld occurred in the system, where the highest amount of lignin was used in hybrid filler MgO-L (1:5 w/w). From mechanical tests of welds, a sharp increase in ultimate seal force was noticed for almost all compositions with lignin, especially where MgO was coupled with a high lignin content. For those composition seal open force raised up to 37.0 N, from the value of 23.6 N, achieved for neat low density polyethylene (LDPE). Tear strength of weld sheets confirmed once more that LDPE composition with MgO-L (1:5 w/w) achieved the highest ultimate force with its value of 71.5 N, and it was ~20.0 N higher than in the case of neat LDPE.